The Teacher's Use of Gesture and Speech in a British Sitcom - Sugianto, Ahmad; Prasetyo, Ilham Agung; Asti, Widy (International Journal of Systemic Functional Linguistics, 2022)
Gestures alongside language constitute one of the essential semiotic resources in an English classroom interaction. It is based on the credence that the meaning-making in any English classroom discourse is realised not only through a language as a semiotic resource, but gestures constitute the other determinant semiotic resources that might facilitate the effective instructional practices and assist students’ English learning. However, scant scrutiny of the way a native English teacher uses gestures in an EFL classroom setting was still found. Thus, the present study aimed to investigate one of the British sitcoms, Mind Your Language. This film is worth investigating for it tells about a native English teacher teaching pupils with multicultural backgrounds. A systemic functional multimodal discourse analysis (SF-MDA) focusing on the ideational metafunction was employed to analyse the artifact, the British sitcom. The findings reveal that various types of gestures were employed by the teacher. Also, the gestures deployed had significant roles and functions, i.e. not only help visualise the lesson learned but also indicate the teacher’s state or condition as well as state during the lesson delivery. Lastly, it suggests that English teachers should take into account the co-contextualising relation between semiotic resources for it might lead students to achieve the expected outcome of the curriculum.